Effect of Guided Inquiry Model by PhET Simulations Worksheet on Science Process Skills and Mastery of Concepts - A. N. Chotimah; D. Setyawarno; D. Rosana (Universitas Negeri Yogyakarta, 2023)
This study aimed to (1) analyze the effect of the science learning of guided inquiry model assisted by PhET Simulations worksheet on science process skills and concept mastery on rope wave material at SMP Negeri 1 Sedayu and (2) analyze the magnitude of the effect of science learning through the guided inquiry model assisted by PhET Simulations worksheet on science process skills and concept mastery on rope waves material at SMP Negeri 1 Sedayu. This study is a quasi-experiment research with a nonequivalent pretest-posttest control group design. The population were seven classes in grade VIII at SMP Negeri 1 Sedayu. The sample were 50 students who were determined by purposive sampling technique. Data collection was observation and test techniques. Data analysis was carried out using descriptive analysis, independent sample t-test, MANOVA test, and effect size. The results showed that (1) there was a significant effect of the guided inquiry learning model assisted by the PhET Simulations worksheet on science process skills and concept mastery on rope wave material (sig. 0.000). and (2) the effect size value in the experiment class with the guided inquiry model assisted by the PhET Simulations worksheet on science process skills and concept mastery in rope wave material is relatively high (1.32 0.8).